Adherence to a healthy sleep pattern is associated with lower risks of all‐cause, cardiovascular and cancer‐specific mortality. (2nd August 2021) - Zhou, Tao; Yuan, Yu; Xue, Qiaochu; Li, Xiang; Wang, Mengying; Ma, Hao; Heianza, Yoriko; Qi, Lu
Abstract: Background: Individual unhealthy sleep behaviours have been associated with increased risks of all‐cause mortality and deaths due to cardiovascular disease (CVD) or cancer. The evidence regarding the association of sleep patterns with these risks is limited. Objective: To examine the associations of sleep patterns with all‐cause, CVD and cancer mortality in a large prospective cohort. Methods: This prospective cohort study included 283, 443 adults from UK Biobank without CVD and cancer at baseline. We created a healthy sleep score and sleep patterns combining five individual sleep behaviours. Results: During a mean (standard deviation) of 8.9 (1.1) years (2.5 million person‐years) of follow up, a total of 7936 all‐cause deaths, 762 CVD‐caused deaths, and 4540 cancer‐caused deaths occurred during follow up. One point increase of the healthy sleep score was associated with a 4–11% lower risk of all‐cause mortality (Hazard Ratio [HR], 0.94; 95% CI, 0.92–0.96), CVD mortality (HR, 0.89; 95% CI, 0.83–0.95) and cancer mortality (HR, 0.96; 95% CI, 0.93–0.99), with adjustment for age, sex, assessment centres, smoking status, alcohol intake status, socioeconomic status and physical activity. Compared with participants with an unfavourable sleep pattern, those with a favourable sleep pattern had 24–42% lower risks of all‐cause and CVD mortality. The association with all‐cause mortality tended to be stronger among underweight participants and those with insufficient physical activity. Conclusions: A healthy sleep pattern was associated with lower risks of all‐cause mortality and mortality from CVD and cancer. Our findings highlight the importance of improving overall sleep behaviours in lowering mortality. Abstract :